ANALISIS ANTESEDEN DAN KONSEKUEN PENGEMBANGAN KARIR KARYAWAN PT PLN APJ SURAKARTA - Santoso, Joko; Cahyono, Edi (Riset Manajemen & Akuntansi, 2013)
The purpose of this study was to examine the antecedent and consequent analysis of career development. This study is hypothesis testing survey method. The population in this study were all employees of PT PLN APJ Surakarta. The samples taken are 64 employees. The analytical tool used to test the suitability of the proposed model and hypotheses is to use a regression method with the help of SPSS 16. The conclusion is the fourth hypothesis was all supported. This indicates that the effect career planning on career development and career management influence on career development. Career development effect on job satisfaction. Career development effect on career commitment. PT PLN APJ Surakarta should increasingly provide career opportunities so that employees can improve planning and career management that can enhance career development thus expected to create job commitment and job satisfaction is high.